The binary and opposite nature of the dyad in the mythical consciousness (Eurasian Journal of Philology Science and Education, 2018)
The article analyzes the opposite qualities and unity of the dyad of the mythical world from the point of view of language and aspects inherent to the nature of the essence of the myth of binary opposition. The binary opposition is considered as a separate category and characterized as the main principle of nature and culture existence. In the article it said that in order to identify subconscious structure it is necessary to study the culture, mentality and spirit of a nation, the structure can certainly recognize the binary opposition. Conclusions are justified by the judgment in the examples that vividly demonstrate the fact that mytheme has formed the basis of a binary opposition. The conclusions in the article also argue that the structure of the binary dyad has a special place in the mythological world view of mythical stories of the peoples of the world and in a poetic space as well.